Malaria Pigment Hemozoin Impairs GM-CSF Receptor Expression and Function by 4-Hydroxynonenal - Oleksii Skorokhod; Valentina Barrera; Giorgia Mandili; Federica Costanza; Elena Valente; Daniela Ulliers; Evelin Schwarzer (MDPI AG, 2021)
Malarial pigment hemozoin (HZ) generates the lipoperoxidation product 4-hydroxynonenal (4-HNE), which is known to cause dysregulation of the immune response in malaria. The inhibition of granulocyte macrophage colony-stimulating factor (GM-CSF)-dependent differentiation of dendritic cells (DC) by HZ and 4-HNE was previously described in vitro, and the GM-CSF receptor (GM-CSF R) was hypothesised to be a primary target of 4-HNE in monocytes. In this study, we show the functional impact of HZ on GM-CSF R in monocytes and monocyte-derived DC by (i) impairing GM-CSF binding by 50 ± 9% and 65 ± 14%, respectively (n = 3 for both cell types); (ii) decreasing the expression of GM-CSF R functional subunit (CD116) on monocyte's surface by 36 ± 11% (n = 6) and in cell lysate by 58 ± 16% (n = 3); and (iii) binding of 4-HNE to distinct amino acid residues on CD116. The data suggest that defective DC differentiation in malaria is caused by GM-CSF R dysregulation and GM-CSF R modification by lipoperoxidation product 4-HNE via direct interaction with its CD116 subunit.